07 Mitochondrial hexokinase II is essential for cardiac function and ischaemic preconditioning. Issue 24 (24th November 2011) - Smeele, K M; Southworth, R; Wu, R; Xie, C; Nederlof, R; Warley, A; Koeman, A; Eerbeek, O; Akar, F; Ardehali, H; Hollmann, M W; Zuurbier, C J
Abstract : Rationale: Isoforms I and II of the glycolytic enzyme hexokinase (HK) are known to associate with mitochondria. It is unknown whether mitochondrially bound hexokinase (mitoHK) is mandatory for ischaemic preconditioning and normal functioning of the intact, beating heart. Objective: We hypothesise that reducing mitoHK abrogates ischaemic preconditioning and disrupts myocardial function. Methods and Results: Ex vivo perfused HKII± hearts exhibited increased cell death following ischaemia (I) and reperfusion (R) injury as compared to WT hearts. However, IPC was unaffected. To investigate acute reductions in mitoHKII levels, WT hearts were treated with a TAT-control peptide or a TAT-HK peptide containing the binding motif of HKII to mitochondria, thereby disrupting mitoHKII association. MitoHK was determined by HKI and HKII immunogold labelling and EM analysis. Low-dose (200 nmol/l) TAT-HK treatment significantly decreased mitoHKII levels without affecting baseline cardiac function, but dramatically increased IR injury and prevented IPC protective effects. Treatment for 15 min with high-dose (10 μmol/l) TAT-HK resulted in acute mitochondrial depolarisation, mitochondrial swelling, profound contractile impairment, and severe cardiac disintegration. The detrimental effects of TAT-HK treatment were re-capitulated by mitochondrial membrane depolarisation following mild mitochondrial uncoupling that does not directly cause mitochondrial permeability transition opening. Conclusion: Acute low-dose dissociation of HKII from mitochondria in heart prevents IPC whereas high-dose HKII dissociation causes cessation of cardiac contraction and tissue disruption, likely through an acute mitochondrial membrane depolarisation mechanism. The results suggest that the association of HKII with mitochondria is essential for IPC protective effects and normal cardiac function through maintenance of mitochondrial potential.